System of Principles for Service in the State Bureau of Investigations (Law and Safety, 2025)
The system of principles governing service in the State Bureau of Investigations is examined. It is noted that service in the State Bureau of Investigations, like any other law enforcement agency, is based on a system of principles. The principles are the basic provisions underlying service and concentratedly reflect the patterns of relevant social relations, permeating the entire mechanism of legal regulation and determining the organisational structure of social relations in the State Bureau of Investigations.The views of scholars on the list of principles of civil service and service in law enforcement agencies have been studied. National legislation that enshrines the principles of civil service and the foundations of the organisation and activities of the State Bureau of Investigations has been researched. Attention is drawn to the lack of unanimity in the approaches of scholars to defining the range of principles of civil service and service in law enforcement agencies, as well as to the differences in the lists of relevant principles in the Ukrainian laws “On Civil Service” and “On the State Bureau of Investigations”.It has been established that the principles of service in the State Bureau of Investigations can be divided into general and special principles. General principles include: the principle of the rule of law; the principle of legality; the principle of justice; the principle of equality; the principle of transparency. Special principles include: the principle of voluntary recruitment; the principle of prohibition of coercion to perform duties not provided for in the contract and job description; the principle of non-partisanship; the principle of patriotism; the principle of impartiality; the principle of ensuring fair, safe and healthy conditions of service; the principle of independence; the principle of professionalism and efficiency; the principle of integrity; the principle of personal safety and social protection; the principle of personal responsibility and inevitability of punishment; the principle of unity of command. The above principles are considered and recommendations for improving the relevant national legislation are proposed.
Keywords: principle; legal regulation; service; employee; law enforcement agencies; work; State Bureau of Investigations.